Linkage analysis in the spinal muscular atrophy type of facioscapulohumeral disease. Issue 8 (August 1989) - Siddique, T; Roper, H; Pericak-Vance, M A; Shaw, J; Warner, K L; Hung, W Y; Phillips, K L; Lunt, P; Cumming, W J; Roses, A D
Abstract : Facioscapulohumeral disease is probably a heterogeneous disorder. We have ascertained and sampled two multigeneration families with the neurogenic form of this disorder, considered to be a type of spinal muscular atrophy (FSHSMA). The two families have 36 affected members. Linkage studies with 10 expressed and seven DNA restriction fragment length polymorphism (RFLP) markers failed to show significant linkage (Zmax greater than or equal to 3.00). However, two areas of probable linkage were defined on chromosomes 1p and 4q with the markers MNS (Zmax = 1.47 at theta max = 0.10) and PGM1 (Zmax = 0.94 at theta max = 0.001) respectively. We are using additional RFLPs from these and other areas of the human genome to screen these families for linkage to FSHSMA.